Intrapartum fetal heart rate and umbilical cord gases as predictors of adverse neonatal outcome: an observational study - Nabiyal, Geetanjali; Sahai, Rashmi M.; Sarbhai, Vinita; Kumar, Rajesh (International Journal of Contemporary Pediatrics, 2025)
Background: Perinatal asphyxia (PA) remains a leading cause of neonatal mortality and long-term neurological impairment, particularly in developing countries, with an incidence of approximately 10 per 1,000 live births. Early detection and timely intervention are crucial. Cardiotocography (CTG) is widely used for intrapartum fetal monitoring, while umbilical arterial blood gas (ABG) analysis accurately reflects the new-born’s metabolic status at birth. Methods: This cross-sectional observational study was conducted at Kasturba Hospital, Delhi, involving 360 term, singleton, low-risk pregnancies in active labor with cephalic presentation. CTG was recorded at admission, rupture of membranes (ROM), and just before delivery. Based on CTG findings, participants were grouped into a control group (n=300) with normal or indeterminate tracings, and a study group (n=60) with abnormal tracings. Paired umbilical cord blood samples were collected for pH and base deficit analysis. Fetal acidosis was defined as umbilical artery (UA) pH <7.1 and umbilical vein (UV) pH <7.2. APGAR scores at 1 and 5 minutes were recorded. NICU-admitted neonates were evaluated for hypoxic-ischemic encephalopathy (HIE) using the Thompson score on days 1, 3, and 5. Results: Abnormal CTG at ROM and before delivery showed significant association with low UA pH, high base deficit, and low UV pH (p<0.001), along with higher NICU admissions. Cord gas parameters also correlated significantly with HIE severity (p=0.024). Conclusions: CTG is an effective intrapartum tool, significantly associated with fetal acidosis and adverse neonatal outcomes.